Does Environmental Initiatives Really Mater My Customers? A Joint Analysis of Performance and Satisfaction Measurement in the Hotel Industry - ROBINOT, Elisabeth (Journal of Environmental Management and Tourism, 2016)
This research note mobilizes Data Envelopment Analysis (DEA) method to build a bridge between consumer satisfactions evaluations of their experience and the economic performance in the hotel industry. Moreover, regarding the particularity of this industry in terms of environmental damages, a focus on environmental initiatives is also integrated to the analysis. By clarifying how green actions lead to performance improvements; this study helps managers defining their most advantageous hotel strategies. Moreover, it enriches the literature by integrating a distinction between satisfaction and specific satisfaction impacts. Results reveals that efficiency increases when the hotel adopt environmental initiatives. Only one hotel on the sample experienced a perfect score in terms of performance and satisfaction. All the transactional satisfaction criterions give a room to help managers identifying the improvement to do in their service delivery experience.
Keywords: green actions; transaction-specific satisfaction; overall satisfaction; performance; efficiency; data envelopment analysis